Meet the parents? The causal effect of family size on the geographic distance between adult children and older parents - Helena Holmlund; Helmut Rainer; Thomas Siedler (Institute for the Study of Labor (IZA), 2009)
An emerging question in demographic economics is whether there is a link between family size and the geographic distance between adult children and elderly parents. Given current population trends, understanding how different configurations of family size and sibship influence patterns of child-parent proximity is vitally important, as it impacts on issues such as intergenerational care and everyday mobility. It may be the case, for example, that larger families enable the responsibility of care for older parents to be shared among more siblings, possibly decreasing individual involvement and relaxing constraints on geographic mobility. However, there is no causal evidence to date on this issue. This study is the first attempt to estimate the causal effect of sibship size on the geographic distance between older parents and adult children by using a large administrative data set from Sweden. We find a positive association between sibship size and child-parent geographic distance. However, when we use multiple births and sibship sex composition as instruments for family size, we do not find any evidence that the observed positive relationship represents a causal effect. Given that family sizes are continuing to fall in many developed countries, our findings suggest that the trend towards smaller families will not necessarily result in adult children being more constrained in terms of their geographic location decisions, at least in countries with extensive state-provision of elderly care.
Keywords: J10; C10; 330; Family size; child-parent geographic proximity; Familie; Eltern; Kinder; Entfernung; Pflegedienst; Schweden